2002
DOI: 10.2139/ssrn.666221
|View full text |Cite
|
Sign up to set email alerts
|

Research on Process Structure for Distributed, Asynchronous Collaborative Writing Groups

Abstract: This paper investigates using higher levels of scripted process structure (procedural explicitness) to improve outcomes of distributed, asynchronous collaborative writing (CW) teams that work on the Internet. This paper reports preliminary results of a one-and-a-half month field experiment on asynchronous collaborative writing using 550 participants. It is found that the highest levels of process structure provide the most benefits to the examined distributed work teams, which has important implications for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Examples of additional research that has been produced include extending this taxonomy using thinkLets for better supporting distributed work for specific writing tasks , improving asynchronous- Greenberg, Gutwin, and Cockburn (1996) and Schlichter, Koch, and Burger (1997). distributed CW groups through increased process structure (Lowry, 2002a), examining proximity effects in asynchronous-distributed CW groups (Lowry, 2002b), and using empirical research to demonstrate Collaboratus' efficacy in providing enhanced group awareness and CW support in synchronous-distributed settings (Lowry & Nunamaker, 2003). In summary, applying a consistent taxonomy and nomenclature to CW tool development helped us create a rich set of requirements and tool possibilities that better addressed the interdisciplinary issues of CW that previous tools did not address.…”
Section: Taxonomy To Technologymentioning
confidence: 99%
“…Examples of additional research that has been produced include extending this taxonomy using thinkLets for better supporting distributed work for specific writing tasks , improving asynchronous- Greenberg, Gutwin, and Cockburn (1996) and Schlichter, Koch, and Burger (1997). distributed CW groups through increased process structure (Lowry, 2002a), examining proximity effects in asynchronous-distributed CW groups (Lowry, 2002b), and using empirical research to demonstrate Collaboratus' efficacy in providing enhanced group awareness and CW support in synchronous-distributed settings (Lowry & Nunamaker, 2003). In summary, applying a consistent taxonomy and nomenclature to CW tool development helped us create a rich set of requirements and tool possibilities that better addressed the interdisciplinary issues of CW that previous tools did not address.…”
Section: Taxonomy To Technologymentioning
confidence: 99%
“…Regarding the organisation of IMS LD which is hierarchically structured, asynchronous collaborative authoring with implicit coordination was considered suitable. Former research has proved that implicit coordination is more suitable for hierarchical tasks or documents rather than explicit coordination (Lowry, 2002;Lowry et al, 2005). Hence, we hypothesise that learning designers do not need intensive communication for coordination.…”
Section: Research Questionsmentioning
confidence: 90%
“…Such facilitated recall procedure does not occur either in the Delphi or the NGT, but publications suggested that compared to unstructured interventions, participants recall the relevant parameters better when procedures are structured during the thinking, visualizing and estimating stage of the interaction with the facilitator [31,32]. Considering that people with motivation or training have been reported to perform better in group interactions [30], we motivated our participants by explaining that they were selected for this discussion from the entire village, and that the information they provided would help develop the right kind of health insurance benefits for them and the entire village.…”
Section: Methodsmentioning
confidence: 99%
“…Delphi and NGT have been found superior to interacting groups for finding solutions to problems [26], but when group interactions were structured to enhance exchanges among the participants during thinking, visualizing and estimating, results were better than with unstructured interactions [31,32]. Moreover, Van de Ven and Delbecq [27] found that the most optimal group processes occurred when a structured procedure entailed interactive discussions after the initial exposé of ideas/views.…”
Section: Introductionmentioning
confidence: 99%